2013
DOI: 10.1093/nar/gkt1153
|View full text |Cite
|
Sign up to set email alerts
|

MultitaskProtDB: a database of multitasking proteins

Abstract: We have compiled MultitaskProtDB, available online at http://wallace.uab.es/multitask, to provide a repository where the many multitasking proteins found in the literature can be stored. Multitasking or moonlighting is the capability of some proteins to execute two or more biological functions. Usually, multitasking proteins are experimentally revealed by serendipity. This ability of proteins to perform multitasking functions helps us to understand one of the ways used by cells to perform many complex function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 31 publications
2
50
0
4
Order By: Relevance
“…This observation is consistent with previous reports that many MPs were known primarily as enzymes when their secondary function was discovered (Hern andez et al, 2014;Jeffery, 2003;Mani et al, 2014).…”
Section: Analysis Of Genome-wide Mp Predictionsupporting
confidence: 93%
See 1 more Smart Citation
“…This observation is consistent with previous reports that many MPs were known primarily as enzymes when their secondary function was discovered (Hern andez et al, 2014;Jeffery, 2003;Mani et al, 2014).…”
Section: Analysis Of Genome-wide Mp Predictionsupporting
confidence: 93%
“…Studies suggest significant impacts of MPs in diseases and disorders (Ov adi, 2011;Sriram et al, 2005) as well as roles in important biochemical pathways (Jeffery, 2004). Despite the potential abundance of MPs in various genomes and their important roles in pathways and disease developments, the size of existing databases (Hern andez et al, 2014;Mani et al, 2014) that contain experimentally confirmed MPs is still too small to obtain a comprehensive picture of the cellular mechanisms underlying their functional diversity. This quantitative insufficiency is due in large part to the tendency for the additional function of these proteins to be found serendipitously in the course of unrelated experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The identified 33 moonlighting proteins (Table 1) and 10 multi-domain multi-function proteins ( Table 2) do not have many overlap with the MoonProt database [79] and MultitaskProtDB [80]. Only two (PepA and DegP) in Table 1 and one (NadR) in Table 2 were found in the two databases.…”
Section: Relmentioning
confidence: 99%
“…The development of databases specifically devoted to moonlighting proteins will increase the accessibility of data on such proteins and facilitate the tracking of new additions to this category. Two such databases have recently been made available, Moonprot (5) and MultitaskProtDB (17). When it appeared, the first one, searchable at http://www .moonlightingproteins.org, presented information on more than 200 moonlighting proteins experimentally verified to behave as such; at its publication, the second one, accessible at http://wallace .uab.es/multitask, offered different information on about 300 multitasking proteins.…”
Section: Databases and Prediction Of Moonlighting Functionsmentioning
confidence: 99%
“…It may be noted that the word "moonlighting" had been used already in 1978 by Freedman to refer to multifunctional proteins in an article entitled "Moonlighting Molecules" (16). Moonlighting proteins are found in diverse organisms, and current dedicated databases list several hundred of them, distributed among the different biological kingdoms (5,17). Their noncanonical roles cover a bewildering array of functions such as control of transcription, protection of DNA, assembly of organelles, chaperoning, splicing of introns, or binding to plasminogen (12,(18)(19)(20).…”
mentioning
confidence: 99%